Najib Mahfuz’s Thought: Approach to A Change of Role of Egyptian Women in Thulathiyah (Trilogy) - Bermawy Munthe (Universitas Islam Negeri Sunan Kalijaga, 2018)
The object of this article is a novel of Najib Mahfuz entitled al-Thula@thiyah by utilizing the formal object of genesis structuralism theory, which states that an article especially a masterpiece is an expression of the writers’ view on the world, the human facts, the collective subject, and a historicity. This article has found that Najib Mahfuz indirectly states in his masterpiece al-Thula@thiyah that the change from traditional roles of the Egyptian women into the social roles of the Egyptian new women might be based on three pillars of approaches having mutual synergy those are the evolutionary and gradual approach, the assertive and persuasive approach, and the education process approach. Applying those three approaches, Najib examines that the change and improvement of the Egyptian new women require a long process divided into three generations as follows: Bain al-Qasrain generation (October 1917 – April 1919), Qasr al-Shauq generation (July 1924 – August 1927), and al-Sukkariyah generation (January 1935 – 1944). Najib Mahfuz examines that the change in the Eygptian women is an absoluteness that is through a polite education. Moreover, he examines that higher education for women is life necessities for their future time. According to Najib Mahfuz, the vision of education is one bridge of change although this opportunity has not been opened yet for the third generation of Egyptian women. They think that high education is divided into four perspectives as follows: it is the life necessities, it is a prohibition although it gives opportunities, it may cause difficulties in finding a husband especially for those who are not beautiful, and it is not a must because the basic education is enough.",